SUONO / Muhammad Nur Amirul Mohd Ruslan - Mohd Ruslan, Muhammad Nur Amirul (Universiti Teknologi MARA, Kedah, 2018)
Music and humans can't be tear apart . On this semester, i learnded about reversed engineeeng IDT 260. I have fo rede-sign an existing portabel speaker Into a new form of minimalism pattial style . On this subject also i have learnd a pragmatic and sy ntho tic analysis. The concept of minimalist arch,cture ism strip everythhing down to its essential quality and thieve simplicity. The design concept that i apply on my project is designing a new design of PO. ble speaker for designer wi. simple and Nogg...dn. My design criteria is to designing a that looks with simple form , small and easy to bring anywhere, My design objectives are to improve the new form of portablg opseInteta:d to ensure the' illitrfUlatax Splbglier d user friendly. Why OIRTV to redesign an exishirtErkbecause of problem agenggicIligri: that i have seen., 18Asliifig product rnay be loolgliller§g„ogicl old also the calogkial.ltykisling Product is sit 040acessary. The target malice{ iTkr rny speaker is designer . Design influence and target user I lake-from the currently nowdays lifestyle . I named my new portable speaker 'SUONO" it is sound from halloo word.